Influence of educational level on HIV/AIDS related knowledge, attitude and sexual behaviour of road transport workers in Ibadan (2008)
This is a non-experimental, exploratory analytical study that investigated some factors that affect the HIV/AIDS related knowledge, attitude and sexual behaviour of road transport workers in Ibadan. A total of 223 commercial road transporters were randomly selected from six motor parks in Ibadan metropolis were used as samples for the study. A self designed and validated scale (Road Transporters HIV/AIDS Related Knowledge, Attitude and Sexual Behaviour Scale) was used to collect data for the study. The data collected were analyzed using one-way analysis of variance. The three hypotheses raised and tested at 0.05 alpha level were rejected (p<0.05) because educational qualifications had significant influence on the HIV/AIDS related knowledge, attitude and sexual behaviours of the commercial road transport workers in Ibadan. The study concluded that formal education plays an important role in the HIV/AIDS related knowledge, attitude and sexual behaviour of the commercial road transport workers and recommended that since education is a vital tool for behaviour modification, a means should be devised in collaboration with NURTW executives to make it mandatory for road transport workers to have at least a secondary school certificate before being allowed to join the union.